Ukrainian Intelligentsia in Post-Soviet L'viv: Narratives, Identity, and Power - Narvselius, Eleonora (Lexington Books, 2012)
Intelligentsia assumes the right to speak in the name of the entire nation and to extrapolate its own tastes, values and choices to it. Therefore, intelligentsia's voices have been in many ways decisive in the discussions about Ukrainian national identity, which gained momentum in the post-Soviet Ukrainian society. The historical and cultural cityscape of L'viv is an especially apt site for investigation of the nexus intelligentsia-nation not only in the Ukrainian, but in the East-Central European context. This borderline city, while not being a remarkable industrial, administrative or political centre, has acquired the reputation of a site of unique cultural production and a principal center of the Ukrainian nationalist movement throughout the twentieth century. Here the popular conceptions of intelligentsia have been elaborated at the intersection of various cultural, historical and political traditions. This study addresses Ukrainian-speaking intelligentsia and intellectuals in L'viv both as a discursive phenomenon and as the social category of cultural producers who in the new circumstances both articulate the nation and are articulated by it.